Application of biocontrol products Bio P60 and Bio T10 as single or in combination in suppressing chili fruit anthracnose in the field - Endang Mugiastuti; Fitrian Hidayat; Murti Wisnu Ragil Sastyawan; Ni Wayan Anik Leana; Loekas Soesanto (Universitas Lampung, 2025)
This study aimed to evaluate the effectiveness of single or combined applications of Bio P60 and Bio T10 products in suppressing anthracnose disease in chili pepper under field conditions. The research was conducted at an altitude of 1200 m above sea level using a randomized block design with five treatments: control, chemical fungicide, Bio P60, Bio T10, and a combination of Bio P60 and Bio T10, each replicated five times. Observed variables included incubation period, disease incidence, disease intensity, area under disease progress curve (AUDPC), infection rate, plant height, number of leaves, time of first flower, time of first fruit, number of fruits, fruit weight per plant, harvest weight per plot, and qualitative phenolic compound content. The results showed that the combined application of Bio P60 and Bio T10 was the most effective, delaying the incubation period, suppressing disease intensity, and reducing AUDPC by 13.71%, 69.34%, and 47.06%, respectively, compared to the control. The combination treatment also enhanced plant growth and yield, increasing plant height, number of fruits, fruit weight per plant, and harvest weight per plot by 27.38%, 62.65%, 90.85%, and 82.99%, respectively. Furthermore, the application of Bio P60, Bio T10, and their combination increased phenolic compound content qualitatively in chili pepper plants.